Cover, Content, and Editorial Note from Daun J Pertanian Kehutanan Vol. 11 No. 1 Juni 2024: Cover, Content, and Editorial Note from Daun J Pertanian Kehutanan Vol. 11 No. 1 Juni 2024 - Daun J Pertanian Kehutanan, Chief Editor of (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Chief Editor of Daun J Pertanian Kehutanan